Experimental Evidence on Preferences for Information - Florian Zimmermann (Verein für Socialpolitik, 2010)
In a recent paper, Koszegi and Rabin (2009) make a novel prediction about people's attitudes towards noninstrumental information, i.e. information about fixed but unknown future outcomes. People prefer to get information clumped together rather than piecewise. We use a controlled lab experiment to examine this prediction. With three different experimental designs, we find no evidence in support of the model by Koszegi and Rabin.
Keywords: C91; D01; D80; 330